Single Sign On Using Keycloak Integrated Public Key Infrastructure for User Authentication In Indonesia’s Electronic Based Government System - Wawan Hermawan (Universitas PGRI Semarang, 2023)
The government in carrying out its function as a public administration servant is regulated in law of the Republic of Indonesia number 25/2009 on public services. In this regulated about electronic government (e-government), many individuals use various web applications that require users to authenticate themselves to access each application. Many entities require various web- based applications for operational activities. This makes centralized access management for web-based applications very much needed. Currently, access management is often implemented using Single Sign On (SSO) with password authentication method. Security considerations arise against the use of passwords. This is because passwords have a vulnerability to brute forcing using a password list, and human nature often uses repeated or uncomplicated passwords. There is an alternative authentication method, namely Mutual TLS which utilizes Public Key Infrastructure (PKI). Users authenticate with X.509 digital certificates, so the authentication factor becomes something you have. This research aims to implement an integrated PKI SSO system and RBAC access automation. The approach of this project is research, design, implementation, and testing. The entire system is built with open-source software and implemented on a cloud infrastructure. The system has three subsystems, namely registration, login and RBAC access automation. All subsystems are tested according to the specified flow. The test results show that the registration subsystem has been successfully carried out as evidenced by the success of filling in personal data, approval flow, and downloading of certificates. The login subsystem was also successfully implemented, as evidenced by the existence of mTLS authentication with certificate validation. In testing the RBAC access automation subsystem, it is shown that the script created can perform access checks and access remediation if needed.